Designing Standard Operating Procedures (SOP) With PDCA Method On Kaconk Flasher Gadget Repair - Fatahilah, Achmad (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to find solutions to the causes of problems in terms of quality experienced and produce business process SOP for Kaconk flasher services. Design/methodology/approach: The draft SOP comes from operating standards that have been agreed upon through FGD and is revised based on the results of the known improvement plan, so that the draft SOP is more perfect before being frozen into a written SOP. Validation of the draft SOP document was carried out by giving questionnaires to customers with a sample size of 13 respondents, namely kaconk flasher customers who visited one week after the implementation of the draft SOP to be tested. Findings: The results of this research show that: Designing SOPs for the kaconk flasher business process, a number of SOPs can be formed which are grouped into several stages, including KF-SOP-01 regarding customer reception services, KF-SOP-02 regarding gadget repair, KF-SOP-03 regarding unit storage in the warehouse , and KF-SOP-04 regarding unit pick-up services. Research limitations/implications: The limitations in this research are the basis for recommendations for future researchers to further develop improvements to the SOP that has been formed from the problems experienced. The limitations of this research are only to find out the root of the problem and its repairs and form an SOP from the results of repairs that have been carried out at the kaconk flasher counter.. Practical implications: All SOPs were implemented successfully and were able to overcome the root of the problem at the Kaconk flasher service center. Originality/value: The research carried out by the researcher states that this research is the result of his work and is the first time at Konter Kaconk Flasher with the title of the research being researched, except for quotations from several summaries, all of which the researcher has explained the source. Paper type: Research paper